Twenty years of Paleohispanistics. Bibliometric and historiographical analysis of Palaeohispanica (2001-2021) in the context of Spanish journals on languages and cultures of ancient Hispania (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This paper presents a bibliometric and historiographical study of Palaeohispanica journal in the first two decades of its history (2001-2021), analyzing its position as an international reference journal in the field of Paleohispanistics. Its main bibliometric indicators (authorship, internationalization, thematic scope) are analyzed, as well as its presence in documentary databases, and its quality indices, in the context of Spanish journals on the languages and cultures of ancient Hispania. This study allows us to conclude that Palaeohispanica has become, due to the quantity and impact of the works published in it since its creation, one of the main scientific journals in its field.
Keywords: Palaeohispanistics; Historiography; Bibliometrics; Journals; Journals Evaluation